Prototype Design Mini Crane Simulator as Viewer Tool Safety Accidents in Dojo PT XYZ - Tri Tjiptadi, Agung; Debora, Fransisca; Rozi , Sayyid Fahru; Arya , Rizki (Journal Knowledge Industrial Engineering (JKIE), 2021)
Occupational safety and health (OHS) is an important aspect of the world of work that must be fulfilled by companies. One of the ways that companies do to meet these needs is by providing training to employees in the form of work accident simulations which aim to allow employees to analyze accidents that arise due to work activities. PT. XYZ is a company that has work activities, one of which is moving goods using a crane, so the company is obliged to provide information on work accidents that can occur in this activity. This study aims to design a tool as a simulation for activities using this crane with the method used is Research and Development. Designing a mini crane simulator prototype as a prop for work accidents at PT. XYZ was developed based on Arduino with the use of an Infrared sensor which will cancel the light if the light is obstructed by an object and make crane activity stop so that work accidents can be overcome. The use of this Mini Crane Simulator is placed in the Safety Dojo which is a training venue. Further and further research on this tool is still needed and tailored to the needs of the company.